John Blacking: a personal tribute - Ballantine, Christopher (International Library of African Music, 1992)
John Blacking was sixty one when he died on 24 January, 1990. I knew him for the last twenty five of those years: first as one of my teachers, soon as a loyal friend, fmally as a colleague. The boundaries between these were never rigid - not even when I was an undergraduate and he a lecturer (and then Professor of Social Anthropology) at the U Diversity of the Witwatersrand.
Keywords: African Music